Seasonal and Spatial Dynamics of Freshwater Snails and Schistosomiasis in Mizan Aman, Southwest Ethiopia - Asrat Meleko; Naomi Caplan; Dorin Brener Turgeman; Azeb Seifu; Zvi Bentwich; Michal Bruck; Nisan Z. Kesete; Willemijn Zaadnoordijk; Noa Dahan (Parasitologia, 2025)
Introduction: Freshwater snails, particularly snails from the genus Biomphalaria, play a key role in the transmission of schistosomiasis, a parasitic disease prevalent in tropical regions. Schistosomiasis poses a significant public health challenge in these regions, leading to chronic illness, reduced productivity, and impaired childhood development, particularly in communities with limited access to healthcare and sanitation. Understanding the seasonal and spatial variations in snail populations and infection rates is crucial for controlling schistosomiasis, especially in areas like Southwest Ethiopia, where the disease burden is high. Methods: This study was conducted in Mizan Aman, Southwest Ethiopia, across two seasons, dry and wet. A total of 1150 snail samples were collected from 20 freshwater sites, and their species, abundance, and infection status were assessed. Environmental parameters, including temperature, pH, salinity, and conductivity, were measured to analyze their impact on snail populations. Results: Four snail species were identified, Biomphalaria pfeifferi, Biomphalaria sudanica, Lymnaea natalensis, and Bulinus globosus, with B. pfeifferi and B. sudanica being the most prevalent. Snail abundance varied by site and season, with 598 in the dry season and 552 in the wet season. Snail abundance and species composition showed significant spatial variation, with higher counts in sites like Sasin and Agu 1, while some sites had no snails. Biomphalaria snails, particularly B. pfeifferi, are the principal intermediate host for Schistosoma mansoni. The overall prevalence of Biomphalaria snails exceeded 85% in both seasons, and their average infection rate in Mizan Aman was 13.5%. This infection rate showed a strong correlation (r = 0.733, p < 0.001) with the incidence of schistosomiasis cases in the community. Seasonal variation in environmental factors, such as temperature and pH, had no significant effect on snail abundance; however, water salinity showed to be correlated with snail abundance during the dry season. Furthermore, community-led vegetation clearance at selected sites significantly reduced snail abundance. Conclusions: This study highlights the seasonal and spatial dynamics of freshwater snails, particularly Biomphalaria species, in relation to schistosomiasis transmission in Mizan Aman, Southwest Ethiopia. The findings confirm that B. pfeifferi species is the predominant intermediate host for schistosoma in this region and that schistosomiasis infection rates among snails significantly correlate with human cases in the community. While environmental factors such as temperature and pH showed no significant influence on snail abundance, water salinity had an impact during the dry season. Additionally, community-led vegetation clearance was an effective intervention in reducing snail populations. These results emphasize the need for targeted, site-specific control measures integrating ecological and community-based interventions to sustainably reduce schistosomiasis transmission.